2021
DOI: 10.1002/eji.202048857
|View full text |Cite
|
Sign up to set email alerts
|

Mass cytometry analysis of blood immune cells from psoriasis patients on biological therapy

Abstract: Psoriasis is a chronic immune‐mediated skin disease accompanied by systemic inflammation and comorbidities. We analyzed peripheral blood mononuclear cells (PBMCs) in the search for immune signatures and biomarkers related to psoriasis severity and treatment effect. Thirty‐two patients with psoriasis and 10 matched healthy controls were included. PBMCs were collected before and after initiation of anti‐TNF, anti‐IL‐17 or anti‐IL‐12/23 treatment and analyzed utilizing 26‐parameter mass cytometry. The number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…In recent studies, methotrexate has been found to decrease Th17, Th1 cell percentages in blood and restore Treg populations and their immunosuppressive function in patients with psoriasis [ 39 , 40 ]. Also, small molecule and biologic therapies have been shown to increase Th2, Treg cell populations and decrease Th1, Th9, and Th22 cells in blood of patients after treatment [ 12 , 41 ]. Previously, our group has demonstrated that apremilast, a phosphodiesterase 4 inhibitor successfully used for the treatment of the disorder, increases IL-10 producing regulatory B cells and decreases IFNγ and IL-17 producing pro inflammatory T subsets in psoriasis and psoriatic arthritis patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, methotrexate has been found to decrease Th17, Th1 cell percentages in blood and restore Treg populations and their immunosuppressive function in patients with psoriasis [ 39 , 40 ]. Also, small molecule and biologic therapies have been shown to increase Th2, Treg cell populations and decrease Th1, Th9, and Th22 cells in blood of patients after treatment [ 12 , 41 ]. Previously, our group has demonstrated that apremilast, a phosphodiesterase 4 inhibitor successfully used for the treatment of the disorder, increases IL-10 producing regulatory B cells and decreases IFNγ and IL-17 producing pro inflammatory T subsets in psoriasis and psoriatic arthritis patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CyTOF technology allowed us to profile the T cell landscape in psoriasis patients comprehensively. Consistent with previous studies (Guo et al, 2019;Solberg et al, 2021), we observed significant alterations in the T cell repertoire of psoriasis patients compared to healthy individuals. The profound differences in T cell subsets and their metabolic states emphasize the systemic nature of psoriasis and provide valuable insights into the pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…CD4 + T helper (T H ) cells orchestrate skin inflammation in psoriasis [ 195 ]. Both skin-infiltrating and circulating T H cells in psoriasis are predominantly T H 1, T H 9, T H 17, and T H 22 cells [ 70 , 197 ].…”
Section: Immune Cells In Psoriasismentioning
confidence: 99%